Paleoglaciology of the central East Antarctic Ice Sheet as revealed by blue-ice sediment. (15th February 2023) - Kaplan, M.R.; Licht, K.J.; Lamp, J.L.; Winckler, G.; Schaefer, J.M.; Graly, J.A.; Kassab, C.M.; Schwartz, R.
Abstract: We present ∼100 cosmogenic surface exposure ages, including 75 new analyses, for a blue-ice moraine complex at Mt. Achernar, head of Law Glacier, in the central Transantarctic Mountains. The 10 Be– 3 He– 26 Al ages along with previously-published boron concentrations chronicle past behavior of the East Antarctic Ice Sheet (EAIS) along the edge of the polar plateau since the sediments started to accumulate, around 0.5–1 Ma. Samples analyzed for 10 Be from the Law Glacier surface record <100 years of exposure, indicating they likely have negligible inheritance when first exposed. The Law Glacier surface experienced relatively minor fluctuations in surface elevation throughout MIS 6 and 5, and likely during prior periods, as geomorphic features are intact and exposure ages are coherent on the moraine, ranging from ∼210 to ∼86 ka; respective means for MIS 5 till in two different areas are 106 ± 9.1 ka [n = 4 ages] and 106 ± 5.1 ka [n = 6]. Although we infer the Law Glacier has been relatively close to its current configuration generally since 0.5–1 Ma, disturbances to Achernar blue-ice moraine architecture seem apparent at times especially prior to the last two glacial cycles. The largest observed disturbance occurred when the nearby Lewis Cliffs Ice Tongue expanded either close to, or earlier than, 500-400 ka. A minimum ice thickness increase of 30 m is associated with the ∼20 ka blue-ice ridges, and a lateral moraine indicates the Law Glacier surface was ∼40–50 m higher at ∼9.2 ± 0.5 ka. Our findings support that lateral accretion over time formed the Mt. Achernar blue-ice moraine sequence, and by implication, other analogue Antarctic deposits. We interpret blue-ice moraines as representing, at times, relatively constant outlet glacier conditions and concur with prior studies that they reflect near-equilibrium forms. Blue-ice sediments are an underutilized and dateable paleoglaciologic and paleoclimate archive in Antarctica, including for former ice surface dynamics and possibly as a repository of old ice during periods such as MIS 5 and prior. Highlights: Paleoglaciology of the central East Antarctic Ice Sheet is revealed by blue-ice sediment. We present ∼100 cosmogenic ages for a blue-ice moraine at Mt. Achernar, central Transantarctic Mountains. The Law Glacier surface experienced relatively minor elevation changes during MIS 6 and 5, and possibly back to ∼0.5 Ma. A lateral moraine indicates the Law Glacier surface was higher at ∼9.2 ± 0.5 ka. Blue-ice sediments are an underutilized and dateable paleoglaciologic and paleoclimate archive.